2015
DOI: 10.3892/or.2015.4245
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant hypomethylation and overexpression of the eyes absent homologue 2 suppresses tumor cell growth of human lung adenocarcinoma cells

Abstract: The eyes absent homologue 2 (EYA2) is a dual-functional transcription factor/phosphatase that plays a critical role in neoplasia. The precise effects of EYA2 remain elusive in non-small cell lung cancer (NSCLC). In the present study, we examined EYA2 expression in NSCLC cell lines and a normal pulmonary epithelial cell line. We found that EYA2 was aberrantly upregulated in the lung adenocarcinoma cells. Therefore, we studied the methylation status of the eya2 gene in a lung adenocarcinoma cell line, a normal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…This result was consistent with a previous study of pancreatic carcinoma . However, the reported correlation in lung cancer cells and breast cancer cells was in contrast to our results. Furthermore, we observed a decrease in the enhancement of proliferation after expression of the H2A.X Y39F mutant (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This result was consistent with a previous study of pancreatic carcinoma . However, the reported correlation in lung cancer cells and breast cancer cells was in contrast to our results. Furthermore, we observed a decrease in the enhancement of proliferation after expression of the H2A.X Y39F mutant (Fig.…”
Section: Resultssupporting
confidence: 89%
“…This result was consistent with a previous study of pancreatic carcinoma [19]. However, the reported correlation in lung cancer cells [20] and breast cancer cells H2A.X Y39ph is involved in the regulation of DDR. (A) Histone proteins were extracted from HCT15 cells after 2 Gy IR exposure.…”
Section: Eya2 Dephosphorylates H2ax Tyr39supporting
confidence: 93%
“… 37 The EYA2 gene is hypomethylated in lung cancer cells, resulting in EYA2 overexpression. 36 We showed that miR-338-3p directly inhibited EYA2 expression at the post-transcriptional level in cultured cancer cells and its expression negatively correlated with EYA2 expression in breast cancer patients. Moreover, we demonstrated that, through EYA2 inhibition, miR-338-3p not only suppressed breast cancer cell proliferation, EMT, migration and invasion in vitro , but also prevented breast cancer cell metastasis to lung in vivo .…”
Section: Discussionmentioning
confidence: 81%
“…33 EYA2 expression has been shown to be overexpressed in a variety of cancers, including breast cancer, ovarian cancer and lung cancer, and its overexpression is correlated with poor prognosis. 34 , 35 , 36 EYA2 increases proliferation, migration, invasion, and metastasis in breast cancer cells. EYA2 is also involved in stimulation of EMT, a process important for cancer cell migration, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…The EYA2 is critical for PLZF-RARA-induced leukemogenesis [ 16 ]. Moreover, EYA2 has been shown to promote cell growth in lung cancer [ 17 ]. EGFR/miR-338-3p/EYA2 axis controls breast tumor growth and lung metastasis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%